COVID-19-associated mucormycosis: Case report and systematic review. Issue 44 (November 2021) - Dilek, Ahmet; Ozaras, Resat; Ozkaya, Sevket; Sunbul, Mustafa; Sen, Elif Itir; Leblebicioglu, Hakan
Abstract: Background: Increasing number of patients with COVID-19-associated mucormycosis have been reported, especially from India recently. We have described a patient with COVID-19-associated mucormycosis and, searched and analyzed current medical literature to delineate the characteristics of COVID-19-associated mucormycosis. Method: We reported a patient developed mucormycosis during post-COVID period. We searched literature to describe the incidence, clinical features, and outcomes of COVID-19-associated mucormycosis. Demographic features, risk factors, clinical features, diagnostic methods, treatment and outcome were analyzed. Results: We describe a 54-year-old male, hospitalized due to severe COVID-19 pneumonia. He was given long-term, high doses of systemic steroids. He developed maxillo-fascial mucormycosis and died of sepsis. Our literature search found 30 publications describing 100 patients including present case report. The majority (n = 68) were reported from India. 76% were male. The most commonly seen risk factors were corticosteroid use (90.5%), diabetes (79%), and hypertension (34%). Also, excessive use of broad-spectrum antibiotics were noted in cases. Most frequent involvements were rhino-orbital (50%), followed by rhino-sinusal (17%), and rhino-orbito-cerebral (15%). Death was reported as 33 out of 99 patients (33, 3%). Conclusions: Steroid use, diabetes, environmental conditions, excessive use of antibiotics, and hypoxia are main risk factors. Despite medical and surgical treatment, mortality rate is high. A multidisciplinary approach is essential to improve the conditions facilitating the emergence of COVID-19-associated mucormycosis. Highlights: Increasing numbers of patients with COVID-19-associated mucormycosis have been reported. The majority of the patients with COVID-19-associated mucormycosis are reported from India. Uncontrolled diabetes, environmental conditions, steroid use, excessive use of antibiotics, and hypoxia are main risk factors. Despite pharmacological and surgical treatment, mortality rate is high.